2010
DOI: 10.1002/iub.320
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone (PTH) peptides through the regulation of hyaluronan metabolism affect osteosarcoma cell migration

Abstract: SummaryParathyroid hormone (PTH) strongly stimulates hyaluronan (HA) synthesis and secretion of both normal and carcinogenic cells of the osteoblastic lineage and improves skeletal microarchitecture. HA, a glycosaminoglycan component of the extracellular matrix (ECM), is capable of transmitting ECM-derived signals to regulate cellular function. In this study, we investigated whether the changes of HA metabolism induced by PTH (1-34) and PTH (7-84) peptides in moderately MG-63 and well-differentiated Saos 2 ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…FGF‐2 has previously been shown to affect osteoblast progenitor proliferation and apoptosis rates in a manner that is synergistic with PTH(1–34) action [4]. Our recent study demonstrated that PTH(1–34) modulates osteosarcoma cell migration [19]. In view of the fact that PTH(1–34) and FGF‐2 signaling collaborate to regulate bone cell growth, we hypothesized that FGF‐2 might also participate in PTH(1–34)‐dependent osteosarcoma cell migration.…”
Section: Resultsmentioning
confidence: 99%
“…FGF‐2 has previously been shown to affect osteoblast progenitor proliferation and apoptosis rates in a manner that is synergistic with PTH(1–34) action [4]. Our recent study demonstrated that PTH(1–34) modulates osteosarcoma cell migration [19]. In view of the fact that PTH(1–34) and FGF‐2 signaling collaborate to regulate bone cell growth, we hypothesized that FGF‐2 might also participate in PTH(1–34)‐dependent osteosarcoma cell migration.…”
Section: Resultsmentioning
confidence: 99%
“…PTHrP downregulated expression of proapoptotic Bax and PUMA and upregulated antiapoptotic Bcl-2 and Bcl-xl. Berdiaki et al [67], using MG-63 and SaOS-2 osteosarcoma cell lines, showed that PTH peptides enhanced osteosarcoma cell migration through the regulation of hyaluron metabolism. However, a previous study showed that overexpression of PTHrP in a murine osteoblastic osteosarcoma cell line reduced cell proliferation by 80% [68].…”
Section: Pathogenesismentioning
confidence: 99%
“…Parathyroid hormone (PTH), PTH peptides, as well as the PTH receptor (PTHR) have been shown by multiple reports to enhance OS cell migration and invasion (100, 101). Autocrine motility factor (AMF), a major cell motility-stimulating factor secreted by tumor cells, is associated with tumor metastasis in various human cancers including OS (102).…”
Section: Bone Sarcoma Tumorigenesismentioning
confidence: 99%